Forensic Auditing of Related Party Transactions: A Strategy for Averting Fraud in Zimbabwean Listed Banks - Kapesa, Tonderai (Copernican Journal of Finance & Accounting, 2026)
This paper investigates the role of forensic auditing as a strategy for averting fraud stemming from related party transactions (RPTs) within Zimbabwean banks. The research was motivated by the persistent bank failures experienced in Zimbabwe, frequently linked to non-performing insider loans and related transaction abuses. The study’s objectives are to examine the nature and extent of RPT-related fraud within these institutions, and to assess the potential benefits of engaging forensic auditors to improve compliance with lending limits, enhance financial reporting integrity, and promote overall financial stability. A mixed-methods approach, guided by an interpretivist research philosophy, was employed to gather data from a diverse range of stakeholders. Self-administered questionnaires and semi-structured interviews were used to collect data. The qualitative data obtained from the interviews and documentary analysis was subjected to thematic analysis to identify key patterns and insights. The findings reveal a widespread perception of significant fraud risks associated with RPTs in Zimbabwean banks, often facilitated by manipulation of financial reporting and abuse of management positions. Participants recognized forensic auditing as a valuable tool for detecting and preventing RPT-related fraud, complementing the work of statutory auditors and strengthening overall internal control systems. The study underscores the need for enhanced ethical practices within bank management, stronger corporate governance frameworks, and increased regulatory oversight by the Reserve Bank of Zimbabwe (RBZ). Key recommendations include promoting periodic engagement of forensic auditors, empowering the RBZ to effectively monitor banks, and criminalizing fraudulent activities by bank managers to foster a more robust and resilient banking sector in Zimbabwe.